2012
DOI: 10.1016/j.livsci.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Feedlot performance, feed efficiency reranking, carcass traits, body composition, energy requirements, meat quality and calpain system activity in Nellore steers with low and high residual feed intake

Abstract: a b s t r a c tThe aim was to evaluate growth, carcass traits, feed efficiency reranking, body composition, calpain system activity and meat quality in Nellore steers that were phenotypically ranked for high and low residual feed intake (RFI). Seventy-two Nellore steers (16-21 month-old, 334719 kg BW) had free access to a feedlot diet for 70 d (feeding period 1, P1). Daily dry matter intake (DMI), body weight gain (ADG) and ultrasound carcass traits were measured individually. The 12 lowest and the 12 highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 51 publications
10
50
1
7
Order By: Relevance
“…In the current study no effect of RFI on, or correlations with, carcass fat score were detected, which is supported by the absence of an effect of RFI on final ultrasonic subcutaneous fat depth. These findings agree with those of Gomes et al (2012) for carcass backfat in steers. However, Nkrumah et al (2004) and Basarab et al (2007) found that RFI had a significant positive correlation (r = 0.25, 0.22; respectively) with carcass fat grade.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study no effect of RFI on, or correlations with, carcass fat score were detected, which is supported by the absence of an effect of RFI on final ultrasonic subcutaneous fat depth. These findings agree with those of Gomes et al (2012) for carcass backfat in steers. However, Nkrumah et al (2004) and Basarab et al (2007) found that RFI had a significant positive correlation (r = 0.25, 0.22; respectively) with carcass fat grade.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Bonilha et al (2009) found that low RFI bulls had 14% lighter kidneys than high RFI bulls, although this was not evident in the current study or in that of Basarab et al (2003). In contrast, Mader et al (2009) and Gomes et al (2012) using steers, found no effect of RFI on the weights of any of the visceral organs measured. More recently, Bonilha et al (2013) found no effect of RFI on weights of any visceral organs except kidney weight, where low RFI bulls had 12% lighter kidneys than high RFI bulls.…”
Section: Visceral Organ Weightscontrasting
confidence: 73%
See 1 more Smart Citation
“…Além disso, esse efeito pode ser atribuído ao maior consumo de matéria seca e energia pelos animais ineficientes, e o consumo alimentar além das exigências pode levar ao aumento na deposição de gordura interna. De acordo com Gomes et al (2012), animais eficientes apresentaram menor quantidade de gordura no trato gastrointestinal menor quantidade de gordura pélvica e inguinal. A gordura interna pode ser um importante componente na variação da eficiência em novilhos Nelore e que como a indústria não paga diretamente por esses componentes de carcaça, a redução da conversão alimentar para gordura visceral pode ser desejada (GOMES et al, 2012).…”
Section: Experimento Metabólicounclassified
“…Médias e coeficientes de variação para as características de maciez e cor de carne nos diferentes tempos de maturação (Tabela 4) se encontraram próximas, com poucas exceções, àquelas observadas em outros trabalhos (Tabela 5) usando animais da raça Nelore, Tabapuã, Brahman e Brangus (CURI et al, 2010;GOMES et al, 2012;LOBO-JR. et al, 2012;MAZZUCCO et al, 2010;PFLANZER;FELICIO, 2011;PINTO et al, 2010PINTO et al, , 2011PRINGLE et al, 1997;RIBEIRO et al, 2012;RILEY et al, 2003;SHACKELFORD et al, 1991;SMITH et al, 2009 A maior média para MFI aos 14 dias de maturação neste trabalho (Tabela 4), quando as estruturas celulares da carne estão bem fragilizadas, poderia ser um resultado da velocidade e/ou do aparelho usado durante a homogeneização das amostras (HOPKINS et al, 2000(HOPKINS et al, , 2004. Médias menores para os valores de L* em todos os tempos e médias maiores para os valores de b* nos dias um (1) e sete (7) de maturação (Tabela 4) quando comparados aos outros trabalhos (Tabela 5) poderiam estar associadas com as diferenças de maturidade dos animais, espessura de gordura da carcaça, declínio de pH e temperatura da carcaça e composição físico-química do músculo (FIEMS et al, 2000;ORELLANA et al, 2009;WISE, 1999).…”
Section: Concentração Dos Metabólitos Da Vitamina D 3 No Plasmaunclassified